HOMOPHOBIA AND ‘UN-AMERICANNESS’ AS RISING FACETS OF ISLAMOPHOBIA: AN ANALYSIS OF ORLANDO SHOOTING MEDIA TRANSCRIPTS - Boulahnane, Saad (Journal of Al-Tamaddun, 2019)
The present article analyzes the rising discourses in the Orlando shooting discursive event, which took place on June 12, 2015 in the United States. Deemed constitutive of the American Muslim identity, the new rhetoric of estrangement emerging during the media coverage of the shooting is probed into using Critical Discourse Analysis. Ideological Square theory is adopted to shed light on the mental representations between the notion of the positive, in-group ‘Us’ and that of the negative, out-group ‘Them,’ hence an ideological split between Muslim and non-Muslim Americans. In addition to Van Dijk’s CDA-based tool, the study avails itself of Quantitative Content Analysis as an auxiliary approach to lay the numerical foundation, which consists in providing the occurrences of the statements imbued with the prevailing discourses. The data analyzed were collected from CNN and Fox News via LexisNexis Online Academic Database, and coded and analyzed using Atlas.ti Data Mining software program. The study has resulted in revealing discourses of estrangement subverting America’s proclaimed character religious pluralism and the constitutional ground on which the country is erected. The results and implications can be viewed in the discussed frames serving as a discursive extension of what is labeled ‘war on terror,’ of which the American Muslim community is the major recipient. The analysis is also done against the backdrop of religious pluralism and its suggested notions of tolerance, respect, and integration.